Which ’Ready-Made’ Relations Contribute to the Intra-Enterprise Relation? - Kuczi, Tibor (Szociológiai Szemle, 2024)
In the past decades Hungary’s economy has been controlled by large state-owned enterprises, while private ventures have been uncommon. In the past two to three years, however, the number of private firms has mushroomed. Unfortunately, in many cases, owners of such enterprises do not know how to properly relate to colleagues and to employees. A ll they do know is that they should have different relationships from those of the past. Since entrepreneurialism in Hungary lacks traditions and accumulated experience, the networks of relations within private firms are generally based upon friendships, family relations, and old professional contacts from the former regime. In this paper I seek to answer the question what ‘ready-made’ relations constitute the basis for starting ventures and how these relations change as time passes in the life of the firm. In so doing, I attempt to classify the ventures into types. Since the analysis relies on the meagre basis of interviews with 3 0-40 small and medium-scale entrepreneurs, the types — often linked to a concrete case — will certainly be modified by further experience. The types can thus not be regarded as yielding a taxonomy in the strict sense covering the entire entrepreneurial sphere. I tend to assign the grouping a heuristic role, helping to illumine how those entering the independent sphere build up their firms using ready-made elements, transcending the past and at the same time being linked to it.